Quranic verses in science Psychological and educational (Journal of the College of Basic Education, 2022)
The Holy Quran is Allah book and is considered as the main source of everything and the source of mercy and blessing upon all people who will realize later that it is different from the other heaven books .The Holy Quran includes a full description of the life system and the heaven instructions such as the (social, ideological, spiritual , and economic ones).Such instructions are appropriate for each time and place without any limitations or obstacles . The width of the science horizons in the modern era asserted that the ideological development of the science has some sort of origin in the Glorious Quran because Quran initiated all the principal rules of human life sciences as in psychology. The research aims at the following aspects;Studying what the Islamic sharia (law) and holy tests provide such as the devices and rules used in activating the psychological and pedagogical topics.The psychological and pedagogical theories are those which are submitted to the personal experience which might be right or wrong as well as they might be applied to specific time and place rather than any other time or place .Accordingly, the Islamic theory is supposed to be the comprehensive and global theory because it sprang out of power which is unrestricted to time and place.This study is a humble attempt used to activate the researchers in inducting the Islamic texts from the holy Quran to find out certain ways and methods in fixing many educational and psychological problems.The research also attempts to find out solutions and answers to the following questions:What is personality in the Quranic perspective?What is the social behavior in the Quranic perspective?How is motivation Quranic perspective?And to achieve the aims and objectives of the study, the researcher used three axes to answer the aforementioned questions as:The first axe deals with the concept of “personality “, the second axe deals with the social education theory whereas the third axe tackles the concept of “motivation”.Through the final results the researcher draw out , some recommendations were given such as:It is a must to study the Quranic verses from the very early stages in the preliminary school when the pupil attends to last to college and in all branches.The teacher of the holy Quran must be professional scientifically and he /she must be able to conduct and has a remarkable experience in other sciences.The Quranic verses must be taught for guiding and directing behavior not for memorizing by heart.All syllabus subjects must contain some Quranic verses associated with the topic understudy.